2014
DOI: 10.1093/fampra/cmu008
|View full text |Cite
|
Sign up to set email alerts
|

Interventions focusing on psychosocial risk factors for patients with non-chronic low back pain in primary care--a systematic review

Abstract: Among the wide range of psychosocial risk factors, research has focused mainly on pain beliefs and coping skills, with disappointing results. Extended theoretical models integrating several psychosocial factors and multicomponent interventions are probably required to meet the challenge of LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 61 publications
0
27
0
3
Order By: Relevance
“…The use of health care-outcomes has not been part of the previous studies of the ‘functional-disturbance’-model, but a recent systematic review concluded that a range of information-based or education-based interventions did not produce significant reductions in the use of health care [57]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of health care-outcomes has not been part of the previous studies of the ‘functional-disturbance’-model, but a recent systematic review concluded that a range of information-based or education-based interventions did not produce significant reductions in the use of health care [57]. …”
Section: Discussionmentioning
confidence: 99%
“…A BPS intervention is not regularly implemented by physiotherapists in primary care, however, and the evidence for BPS interventions for patients with CLBP is lacking. Few systematic reviews have investigated the evidence from existing BPS primary care interventions but focused instead only on BPS interventions in patients with LBP in general (ie, acute, subacute, and chronic) or (sub)acute LBP specifically . No systematic review has been performed in patients with CLBP until now.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is good quality evidence for the predictive value of a set of psychosocial factors for poorer outcome in patients with LBP [7, 8]. These factors are multifactorial, interrelated, and only weakly associated to the development and prognosis of LBP [9], which might be one of the explanations why effects of treatments targeting those risk factors has been reported to be small, mostly short term, and there was little evidence that psychosocial treatments were superior to other active treatments [7, 10]. …”
Section: Introductionmentioning
confidence: 99%